COMPETENCE OF HUMAN RESOURCES AND THE GOVERNMENT INTERNAL CONTROL SYSTEM (SPIP) AND THE EFFECTS ON THE FINANCIAL STATEMENT QUALITY OF PUBLIC SERCVICE AGENCY (BLU) MODERATED BY GOVERNMENT ACCOUNTING STANDARD (SAP) - Panjaitan, Inggrid (Jurnal Dinamika Akuntansi, 2016)
The aim of this research is to examine the effects of Human Resources Competence and the Government Internal Control System (SPIP) on the Quality of Financial Statements of the Public Service Agency with the Government Accounting Standard (SAP) as moderating variable. The research was conducted at the Public Service Agency of Government Hospital in Jakarta under the Ministry of Health. The sampling technique in this study used purposive sampling method (sampling intentionally in accordance with the requirements of samples required). Questionnaires were distributed as many as 85 questionnaires to some employees in the finance department and others that related to the making of financial statement at the Public Service Agency of Government Hospital under the Ministry of Health. The results showed that HR Competency significantly affected the quality of Public Service Agency Financial Statement. SPIP significantly affected the quality of Public Service Agency Financial Statement. Moderation of Government Accounting Standard (SAP) significantly affected and weakened the effect of HR Competency on the Quality of Public Service Agency Financial Statement. Moderation of Government Accounting Standards did not affect significant and strengthened the effect of SPIP on the Quality of Public Service Agency Financial Statement.